2017
DOI: 10.1002/bit.26381
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the liquefaction stage of enzyme‐mediated biomass deconstruction

Abstract: Effective enzyme-mediated viscosity reduction, disaggregation, or "liquefaction," is required to overcome the rheological challenges resulting from the fibrous, hygroscopic nature of lignocellulosic biomass, particularly at the high solids loadings that will be required for an economically viable process. However, the actual mechanisms involved in enzyme-mediated liquefaction, as determined by viscosity or yield stress reduction, have yet to be fully resolved. Particle fragmentation, interparticle interaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It is an "auto catalyzed" process, where acetic acid released from hemicellulose and self-ionization of water at elevated temperatures causes a drop in pH which acts as a catalyst (Sharma et al, 2015b). SE has been reported to break down biomass structure and develop pores for higher enzymatic accessibility (van der Zwan et al, 2017). During SE most of the hemicellulose is hydrolyzed to soluble sugar monomers and some fraction of cellulase also gets depolymerized into glucose while, a small fraction of lignin is dissolved and/or redistributed (Kumar and Murthy, 2011;Agrawal et al, 2013b).…”
Section: Wheat Straw Pretreatment and Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an "auto catalyzed" process, where acetic acid released from hemicellulose and self-ionization of water at elevated temperatures causes a drop in pH which acts as a catalyst (Sharma et al, 2015b). SE has been reported to break down biomass structure and develop pores for higher enzymatic accessibility (van der Zwan et al, 2017). During SE most of the hemicellulose is hydrolyzed to soluble sugar monomers and some fraction of cellulase also gets depolymerized into glucose while, a small fraction of lignin is dissolved and/or redistributed (Kumar and Murthy, 2011;Agrawal et al, 2013b).…”
Section: Wheat Straw Pretreatment and Chemical Compositionmentioning
confidence: 99%
“…A few published reports are discussed here inbrief which might be referred for further details. Takano and Hoshino (2018) who optimized the commercial enzyme reagents for hydrolysis of the alkali pretreated rice straw have reported that a combination of "Cellulase Onozuka 3S, " "Cellulase T Amano 4, " and "Pectinase G Amano" improved the hydrolysis efficiency with a yield of 94%. Soleimani and Ranaei-Siadat (2017) reported that an optimize enzyme cocktail optimized via response surface methodology involved enzymes, including Exo-1,4-β-D-glucanases II (CBHII), Endo-1,4-β-D-glucanases II (EGII) and 1,4-β-D-glucosidases I (BGI) improved the degradation of pretreated bagasse.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of microscope images showed that refining caused separation of cells, surface fibrillation, internal delamination and generation of fines. These changes collectively contributed to increased accessible surface area and enhance enzymatic hydrolysis [ 7 , 11 13 ]. Fiber quality analyzer and laser diffraction were used to measure particle size of unrefined and refined biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Water retention values, dye adsorption and differential scanning calorimetry were used to access the effect of mechanical refining on biomass surface area. Refining processes increased cell wall porosity and surface area, which contributed to increase the exposure of carbohydrates to cellulolytic enzymes [ 9 , 10 , 12 , 13 , 15 , 16 ]. The effect of mechanical refining on cellulose crystallinity was also evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, during enzymatic hydrolysis, the viscosity or yield stress of lignocellulose slurries decreases in a process termed "liquefaction, " which occurs through various mechanisms including material dilution, particle fragmentation and modification of interparticle interactions (Roche et al, 2009;Thygesen et al, 2014;van der Zwan et al, 2017). To deal with the high viscosities/yield stresses of concentrated lignocellulose slurries, a separate enzymatic liquefaction stage similar to that used in starch-based biorefineries appears promising (Szijártó et al, 2011a), reducing viscosity/yield stress prior to further saccharification.…”
Section: Introductionmentioning
confidence: 99%